2015
DOI: 10.1007/s00586-015-4269-3
|View full text |Cite
|
Sign up to set email alerts
|

Does hybrid fixation prevent junctional disease after posterior fusion for degenerative lumbar disorders? A minimum 5-year follow-up study

Abstract: Purpose Medium-to long-term retrospective evaluation of clinical and radiographic outcome in the treatment of degenerative lumbar diseases with hybrid posterior fixation. Methods Thirty patients were included with the mean age of 47.8 years (range 35 to 60 years). All patients underwent posterior lumbar instrumentation using hybrid fixation for lumbar stenosis with instability (13 cases), degenerative spondylolisthesis Meyerding grade I (6 cases), degenerative disc disease of one or more adjacent levels in six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…DTO implantation is a good alternative to rigid fixation in the carefully selected patient, being ideal for those patients with critical spinal instability and adjacent level pathology of lesser severity that requires decompression but not necessarily rigid fixation. Overall, data regarding this hybrid system is limited, but some small retrospective reviews indicate that DTO implants can alleviate back pain with ASD reported in 10.0% and 12.5% of patients at five-year and mean eight-month follow-ups, respectively [ 13 - 14 ]. Lee, et al recently compared ASD development between rigid fixation and hybrid fusion to dynamic stabilization at two-year follow-up and found that hybrid systems delayed, but did not prevent, ASD [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…DTO implantation is a good alternative to rigid fixation in the carefully selected patient, being ideal for those patients with critical spinal instability and adjacent level pathology of lesser severity that requires decompression but not necessarily rigid fixation. Overall, data regarding this hybrid system is limited, but some small retrospective reviews indicate that DTO implants can alleviate back pain with ASD reported in 10.0% and 12.5% of patients at five-year and mean eight-month follow-ups, respectively [ 13 - 14 ]. Lee, et al recently compared ASD development between rigid fixation and hybrid fusion to dynamic stabilization at two-year follow-up and found that hybrid systems delayed, but did not prevent, ASD [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of the implants, two required conversion to formal arthrodesis, one became infected, one required the implantation of an intrathecal pump, and two exhibited signs of screw loosening [ 12 ]. More recently, Baioni, et al reported no cases of implant breakage or screw loosening in five-year follow-up with a 30 patient cohort of DTO implants [ 14 ]. In our previous analysis, we reported treatment failure in 12.5% of patients implanted with DTO [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…27,28 Based on this evidence for ASD, the concept of hybrid stabilization comprising rigid fixation and dynamic stabilization has emerged. 2 Hybrid stabilization is generally classified into interspinous device (ISD)-based hybrid stabilization (IH; interspinous process stabilizer with conventional fusion) and pedicle screw-rod-based hybrid stabilization (PH; pedicle screw-rod construct with flexible rod at the adjacent upper segment). Several retrospective clinical studies 1,20,25 have demonstrated the effectiveness of IH and PH in preventing ASD.…”
mentioning
confidence: 99%